A facile and efficient strategy to gram-scale preparation of composition-controllable Ni-Fe LDHs nanosheets for superior OER catalysis. (20th January 2017) - Zhang, Kai; Wang, Wenhai; Kuai, Long; Geng, Baoyou
Graphical abstract: This work proposes a novel and facile co-reduction and subsequent co-oxidation strategy to gram-scale preparation of composition-controllable LDHs nanosheets with top-scale electrocatalytic activity toward OER in alkaline media. Highlights: A facile and efficient method to prepare NiFe-LDHs was presented. Different Ni/Fe proportions of NiFe-LDH were synthesized. The growth mechanism of this method has been discussed. Ni6 Fe4 -LDH shows excellent OER performance in alkaline solution. Chronopotentiometry curves only 0.08 V increased after 3 h' continuous test. Abstract: High-efficient catalysts for oxygen evolution reaction (OER) are crucial to energy storage and conversion between electricity and chemicals. This work proposes a facile co-reduction and subsequent co-oxidation strategy to gram-scale preparation of composition-controllable LDHs nanosheets by a case study of Ni-Fe LDHs. Different from the traditional coprecipitation method, this process does not need heating and pH control. More importantly, our method can make sure that the Ni-Fe proportion in the LDHs products is well consistent with that in the mother solution. Furthermore, the electrocatalytic OER results strongly demonstrate that the as-prepared Ni-Fe LDHs possess a top-scale activity toward OER in alkaline media, typically for the Ni6 Fe4 -LDH nanosheets with water oxidation overpotential as low as 0.24 V at a current density of 20 mA/cm 2 . Besides, it presents excellent stability during the endurance test. Therefore, the co-reduction and subsequent co-oxidation strategy is an highly efficient way to LDHs nanosheets for electrochemical applications.